Eucalypt plantations - Turnbull, J.W. (1999)
This paper reviews the historical development of the use of the eucalypt over 200 years, from its curiosity status in the botanical gardens of Europe to its extensive use as a fuelwood for the wood-burning locomotives of the national railway systems, and then to its more recent use as a major source of biomass for paper pulp, fiberboard, industrial carcoal, and fuelwood. Ecological and biological aspects of the genus Eucalyptus have made it successful as an exotic in industrial monocultures and as a multipurpose tree of benefit to small landholders. Social, policy, and economic aspects of growing Eucalyptus are examined, as are rospects for using the eucalypt in the twenty-first century as an industrial plantation tree and as a component of farming systems in the rural landscape.